Heat transfer characteristics of boundary layer flow on a non-linear porous shrinking sheet with radiation effect - Zuhdi, Ahmad Zaim; Md Ali, Fadzilah (Universiti Putra Malaysia, 2023)
This present study investigates the problem of magnetohydrodynamics (MHD) boundary layer flow over a non-linear porous shrinking sheet. This study is also considered the effect of radiation. Firstly, the governing partial differential equations are reduced to ordinary differential equations by similarity transformations. Then, the transformed equations are been solved by using bvp4c method in Matlab solver in order to obtain numerical solutions for various parameters. Parameters involved in this problem are magnetic parameter, non-dimensional controlling parameter, suction parameter, radiation parameter and Prandtl number. The present results earned are being compared with previous published results and it gives a significant agreement between them. It is found that there exist dual solutions. It is also found that the magnetic parameter delays the thermal boundary layer separation, while the non-dimensional controlling parameter enhances the thermal boundary layer separation. It is also observed that the turning point for various values of radiation parameter occurs at the same value. The impact of radiation on the heat transfer rate at the surface becomes lesser when the radiation parameter increases.